Serological Response in Lung Transplant Recipients after Two Doses of SARS-CoV-2 mRNA Vaccines - Madhusudhanan Narasimhan; Lenin Mahimainathan; Andrew E Clark; Amena Usmani; Jing Cao; Ellen Araj; Fernando Torres; Ravi Sarode; Vaidehi Kaza; Chantale Lacelle; Alagarraju Muthukumar (Vaccines, 2021)
Background: Lung-transplant (LT) recipients are at high risk for COVID-19 due to immunosuppression and respiratory tropism of SARS-CoV-2. The information on the effect of COVID-19 mRNA vaccines to elicit immunogenic responses after a two-dose (2D) regimen in LT recipients is sparse. Thus, we assessed the effect of Pfizer-BioNTech and Moderna mRNA vaccines’ 2D regimen on anti-spike responses in immunocompromised LT recipients. Methods: We utilized serum samples from LT recipients vaccinated for SARS-CoV-2 with 2D of either the Pfizer-BioNTech or Moderna vaccines and 2D-vaccinated naïve (non-transplanted and non-exposed to COVID-19) group. Antibody responses were assessed using the FDA-approved SARS-CoV-2 anti-nucleocapsid protein IgG assay (IgGNC), the SARS-CoV-2 anti-spike protein IgM assay (IgMSP), and the SARS-CoV-2 anti-spike protein IgG II assay (IgGSP). CD4+ T-cell activity was assessed as a marker of immune competence using the ImmuKnow® assay. Results: About 25% (18/73) of SARS-CoV-2 uninfected-LT patients generated a positive spike-IgG response following 2D of vaccines, with 36% (9/25) in the Moderna cohort and only 19% (9/48) in the Pfizer cohort. 2D in LT patients elicited a significantly lesser median IgGSP response (1.7 AU/mL, 95% CI: 0.6–7.5 AU/mL) compared to non-transplanted, uninfected naïve subjects (14,209 AU/mL, 95% CI: 11,261–18,836 AU/mL; p < 0.0001). In LT patients, the Moderna-evoked seropositivity trend was higher than Pfizer. Conclusion: 2D COVID-19 vaccination elicits a dampened serological response in LT patients. Whether assessing other arms of host immunity combined with a higher vaccine dose can better capture and elicit improved immunogenicity in this immunocompromised population warrants investigation.